2021
DOI: 10.15252/embj.2020107346
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated POT1 mutations lead to telomere elongation without induction of a DNA damage response

Abstract: Mutations in the shelterin protein POT1 are associated with chronic lymphocytic leukemia (CLL), Hodgkin lymphoma, angiosarcoma, melanoma, and other cancers. These cancer-associated POT1 (caPOT1) mutations are generally heterozygous, missense, or nonsense mutations occurring throughout the POT1 reading frame. Cancers with caPOT1 mutations have elongated telomeres and show increased genomic instability, but which of the two phenotypes promotes tumorigenesis is unclear. We tested the effects of CAS9-engineered ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 76 publications
(99 reference statements)
1
17
0
Order By: Relevance
“…Compared to the overexpression model, the primary fibroblasts harboring heterozygous POT1 p.Q199* displayed strong telomeric elongation. This is in line with published data from human embryonic stem cells (hESC), in which cancer-associated POT1 mutations did not trigger DNA damage responses but led to longer telomeres [ 21 ]. This telomere elongation is further confirmed by numerous in vitro POT1 knockout and overexpression models [ 5 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Compared to the overexpression model, the primary fibroblasts harboring heterozygous POT1 p.Q199* displayed strong telomeric elongation. This is in line with published data from human embryonic stem cells (hESC), in which cancer-associated POT1 mutations did not trigger DNA damage responses but led to longer telomeres [ 21 ]. This telomere elongation is further confirmed by numerous in vitro POT1 knockout and overexpression models [ 5 , 21 , 22 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, previous reports on POT1 germline variants in other cancers connect POT1 deregulation with telomere elongation [ 26 , 27 ]. Therefore, our findings suggest that germline POT1 haploinsufficiency causes abnormally long telomeres, which might generate a susceptible cell population with extended proliferative capacity and the potential to acquire additional mutations required for malignant transformation [ 21 ]. Likewise, long telomeres are more fragile and pose an increased risk for genomic instabilities, favoring cancer progression [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been shown that telomeric replication stress caused by POT1 dysfunction enables telomeres to travel along nuclear actin filaments to the nuclear periphery, resulting in MiDAS at telomeres in telomerase-positive cells [ 94 , 95 ]. Consistent with replication stress-induced telomere lengthening, POT1 mutations have been identified in a growing number of cancer types, including chronic lymphocytic leukaemia (CLL), melanoma and sarcoma, and are associated with longer telomere lengths [ 96 ]. These discoveries demonstrate the capacity for localized replication stress to promote the repositioning of telomeres and the engagement of telomerase.…”
Section: Telomere Maintenance Is a Replication Stress Responsementioning
confidence: 99%
“…The Q94E mutation has been found in individuals from families with high levels of melanoma and has also been identified as a recurrent somatic mutation that occurs during development of chronic lymphocytic leukemia [187,190]. Expression of several cancer-associated POT1 variants leads to telomere elongation and sometimes to increased telomere fragility [188,191]. The long somatic telomeres caused by human germline POT1 mutations could impede the ability of senescence to suppress tumor development but may also affect DNA damage signaling and recombination at telomeres [192,193].…”
Section: Future Directionsmentioning
confidence: 99%